2014
DOI: 10.3176/oil.2014.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Amount of Estonian Oil Shale Products From Combustion in Regular and Oxy-Fuel Mode in a CFB Boiler

Abstract: Oxy-fuel combustion is considered as one of the promising carbon capture and storage (CCS) technologies for coal-fired boilers. In oxy-fuel combustion, the combustion gases are oxygen and the recirculating flue gas, and the main components of the combustion gas are O 2 , CO 2 and H 2 O [1]. The paper presents the results of the calculation of the flue gas amount during combustion of oil shale using oxy-fuel technology in a circulated fluidized bed (CFB) mode. The calculations were performed for different oil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…In oxy-fuel CFB combustors, sulfation can occur directly without the calcination step (Equation (3)). Theoretical calculations [20][21][22] and a previous study in a lab-scale fluidized bed batch reactor [23] revealed that carbonate minerals do not fully decompose under oxy-fuel combustion environment and the sulfur binding rate decreases, similar to the experiments of Li et al [24]. On the contrary, some other experiments [18,25,26] showed a decrease in sulfur emissions or increased sulfur capture efficiency when applying oxy-combustion.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…In oxy-fuel CFB combustors, sulfation can occur directly without the calcination step (Equation (3)). Theoretical calculations [20][21][22] and a previous study in a lab-scale fluidized bed batch reactor [23] revealed that carbonate minerals do not fully decompose under oxy-fuel combustion environment and the sulfur binding rate decreases, similar to the experiments of Li et al [24]. On the contrary, some other experiments [18,25,26] showed a decrease in sulfur emissions or increased sulfur capture efficiency when applying oxy-combustion.…”
Section: Introductionsupporting
confidence: 78%
“…Of the total carbon in the fuel, 20% was inorganic (see Table 1). It is theoretically possible to reduce the extent of decomposition of carbonate minerals to 28% in an oxy-CFB combustor firing Estonian oil shale [20]. The minimum is defined by the dolomite and sulfur content in the fuel.…”
Section: Ashesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxy-combustion technology was proposed as a means to produce relatively pure CO 2 for enhanced oil recovery (EOR) [5]. This technology is based on combustion of fuel in the presence of high-purity O 2 and partially recycled exhaust gas (to moderate the flame temperature, as combustion in high-purity oxygen would result in intolerably high temperatures in the combustors).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the OS has applications in Estonia and China. In the case of Estonia, the OS is combusted for energy production, using pulverized firing and a circulating fluidizing bed [1][2][3][4][5]. In China, OS is used for oil production [6,7].…”
Section: Introductionmentioning
confidence: 99%